Luans and the Spirit of Time - Azevedo, Murah (Neohumano Audiovisual, 2006)
Verzio FF Submission Copacabana – the district with the highest official rate of street dwellers in Rio de Janeiro, is the documentary’s natural scenario. The film’s backbone is the ambiguous, conflicting and, at times, surreal relationship between the regular inhabitants of the famous district, the street kids and the mass media’s power to shape people’s behavior, especially television. “Luans” invites the viewer to a peculiar journey in this multi-faceted environment.